The effect of body image perceptions on life satisfaction and emotional wellbeing of adolescent students: - Sakellariou, Chris (2023)
Studies investigating specific determinants of subjective wellbeing (such as body image perceptions) using experimental/quasi-experimental methods are lacking. Furthermore, few studies considered more than one dimension of wellbeing, used multi-country samples, or considered a variety of determinants/correlates of wellbeing. Only a small minority of studies are on adolescents. I used a large multi-country sample of 15-year-old students, to implement an innovative methodological approach which accounts for potential endogeneity of body image perceptions and derive estimates of the effect of body image on the cognitive and emotional wellbeing of adolescent students. I supplemented Instrumental Variables (IV) estimation with the newly developed - instrument free estimation method, to derive gender-specific causal effect estimates. The outcome measures considered are Life Satisfaction (0-10 scale) and Positive Affect. I found that biases associated with endogeneity of perceived body image are more important when emotional well-being is considered. Similarly, gender differences in the effect of body image satisfaction were established only on the emotional dimension of wellbeing (Positive Affect); the effect size for girls is about three times larger than for boys.